Diseño e implementación de prototipo de un sistema de seguridad para el encendido y rastreo satelital de un vehículo - Murillo Coello, Bryan Joshua (2015)
The technology constitutes nowadays a significant part of the daily life, being used to improve processes, optimize resources, etc. its use depends on the user´s need for this reason has developed a system that alerts the vehicle´s owner if it has moved from its location without authorization of the same one, with the help of a Global Positioning System (GPS) and developing a script one manager to detect its change of position by sending a text message alerting the event; in addition this system uses a camera located strategically inside the car, this system can take a picture of any strange person that uses the car. Getting to procedure with the necessary measures, this system notifies the authorities the incident in the given time. Another feature that has designed the prototype is the information vehicle satellite tracking maps through a Web page that will access the user with his/her respective authentication, name and password assigned through a computer or smartphones; also it has ability to remotely lock the vehicle. This system is easy to handle and install. Also the user will have less fear to leave his/her car in a parking lot that does not have private security and parking.